ナンキョク エットウ キチ ニ オケル イリョウ ノ コクサイ ヒカク チョウサ - 長谷川, 恭久; ハセガワ, ヤスヒサ; 渡邉, 研太郎; ワタナベ, ケンタロウ; Hasegawa, Yasuhisa; Watanabe, Kentaro (2007)
P(論文) 2005年10月,昭和基地から外国の南極越冬基地に電子メールを送信し,昭和基地を含めた13カ国18基地の医療事情を調査した.対象基地の越冬隊員数は4-37名,平均年齢は36.4歳であった.昭和基地のみが医師2名体制で,他基地は医師1名であった.女性越冬医師は4名で,全越冬医師の22%であった.医療機器の整備状況から約6割の基地で全身麻酔下の手術が可能と考えられた.過去にさかのぼると,9基地で32例の外科手術が行われており,虫垂切除術が14例を占めていた.死亡例は9基地で18例確認され,大部分は事故死で,病死は急性心筋梗塞の2例であった.傷病者の南極外への緊急搬出は11基地で23例あり,傷病別では整形外科疾患11例,急性虫垂炎3例であった. 緊急搬出の多くは夏期の限られた期間に集中し,冬期の搬出は2例であった. In October, 2005, we sent several questions to foreign Antarctic wintering-over stations by e-mail, and made an international comparative study of winter medical services at 18 stations of 13 nations. The number of wintering members at the stations that we investigated was 4-37 persons, and the average age was 36.4 years old. Syowa Station had two medical doctors, and the others had one each. There were 4 female doctors, 22% of all wintering-over doctors. About 60% stations had medical facilities for operations under general-anesthesia. In the past, 32 operations including 14 appendectomies have been performed at 9 stations. There have been 18 deaths at 9 stations. Most were accidental deaths, 2 were caused by acute myocardial infarction. At 11 stations, there were 21 medical evacuations in summer, and 2 in winter, including 11 cases of orthopedic disease and 3 of acute appendicitis. departmental bulletin paper